The effects of nutrient artery ligation on the development of the distal ulnar metaphysis of the dog - Alvarado Morillo, Manuel (Revista Científica de la Facultad de Ciencias Veterinarias)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Helvetica; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:7 0 0 0 147 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:595.3pt 841.9pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> A total of 18 dogs were used in this study. They were obtained from the Veterinary Hospital of the University of Pennsylvania, Comparative Cardiovascular Studies Unit and from a dog pound of the Veterinary Policlinic, University of Zulia, Faculty of Veterinary Sciences. Ablation of the nutrient artery by ligation of the palmar interosseous artery was performed in 10 dogs; 6 one-month-old dogs; 2 two-month-old dogs; 2 three-month-old dogs. Radiographic examination of the forelimbs at a weekly interval was performed in these 10 dogs from one to six weeks postoperatively. The opposite normal front leg was used as a control. Six dogs were sacrificed at one month of age and arteriograms of the forelimbs were made. The radiographic changes observed during the first postoperative week were an increased in density and diameter of the distal ulnar metaphysis, increased width of the distal ulnar physis, and a decrease in length of the ulnar diaphysis. These radiographic changes were observed decreasing in severity during a period of five postoperative weeks. At six weeks postoperatively the distal ulna was similar to the control. Between 3 to 5 weeks postoperatively the metaphyseal density of the ulna was decreased and irregular. The decrease in metaphyseal density resulted from a wedge-shaped retained cartilaginous tissue core wich extended proximally into the metaphysis. A diminished blood supply to that area was observed angiographically and histologically in all dogs. The changes observed in the distal ulnar metaphysis in histologic sections and radiographs are comparable to those observed in the distal metaphysis of the ulna in young giant dogs with retained enchondral cartilage. The radiographic and histological findings observed in this study suggests that the lesion observed in rapidly-growing young giant dogs in the distal ulna is due to a diminished blood supply to the metaphyseal area. The study was designed with the specific objective to determine the effect on bone growth after ablation of the nutrient artery of the ulna of the dog.